IMPLEMENTASI CRIMINAL POLICY TERHADAP PERTANGGUNG JAWABAN KEJAHATAN KORPORASI - Arie Kartika (Universitas Medan Area, 2015)
Not only persoon, corporate can also condemnation because corporation is as the subject of lawand corporate also get benefit of what has been done managers.in this case law imposed must be fought togive the punishment. The implementation of criminal policy so important role and the breadth of corporatecrime. Prevention may be was conducted with two facilities, using penal and non penal. Three theory exactin corporate responsibility system are identification theory, vicarious liability theory ang strict liability.